CHEMO-IMMUNOLOGICAL STUDIES ON CONJUGATED CARBOHYDRATE-PROTEINS : III. ACTIVE AND PASSIVE ANAPHYLAXIS WITH SYNTHETIC SUGAR-PROTEINS - Tillett, William S. (The Rockefeller University Press, 1929)
1. Guinea pigs passively sensitized with the serum of rabbits immunized with an artificially prepared sugar-protein (gluco-globulin) exhibit typical anaphylactic shock when subsequently inoculated with gluco-albumin; the serum of rabbits immunized with a second synthetic sugar-protein (galacto-globulin) similarly sensitizes guinea pigs to galacto-albumin. The reactions, in each instance, are specific and depend for their specificity on the carbohydrate component, and not on the protein fraction of the synthesized sugar-protein. 2. Guinea pigs actively sensitized with gluco-globulin or galacto-globulin are similarly subject to anaphylactic shock, when injected, after 21 days, with sugar-proteins containing carbohydrate identical with that present in the sensitizing antigen, regardless of the kind of protein with which it is combined. 3. The unconjugated glucosides, although themselves not capable of inducing shock, inhibit the anaphylactic reaction when injected immediately prior to the introduction of the toxigenic sugar-protein. The protective action of the glucosides disappears within two hours after injection. In order to elicit the phenomenon, the carbohydrate must be the same as that combined in the sugar-protein complex. 4. Anaphylactic shock may be induced by uncombined globulin in guinea pigs passively sensitized with either antigluco-globulin serum or antigalacto-globulin serum; globulin is similarly effective in animals actively sensitized with gluco-globulin or galacto-globulin. The reactions elicited by globulin alone are dependent upon the common protein present in the antigens, and exhibit only species specificity.